(3eYLR CMeOs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s
(3ChdgG (B:s
(3bGd CHhGdWjH CMeO Hf GdMSjf Gdchaj GdLYaj GdeJfHj QMeg Gddg s
(3BNQgG (B:s
(3agPG GdMRf GdPj HfG jVfjfG hjgRdfG eKd GdehJ GdPj jHdj LSOc hjaQb ChUGdc, afMf CehGJ aj UhQI GdCMjGA s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3HgGeTgG HYV GdJbjjOGJ hGdJYdjbGJs
(3HgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs